A EFFECT OF STRENUOUS PHYSICAL ACTIVITY ON THE SUM OF LEUKOCYTES IN WISTAR STRAIN MALE MICE : A EFFECT OF STRENUOUS PHYSICAL ACTIVITY ON THE SUM OF LEUKOCYTES IN WISTAR STRAIN MALE MICE - Annisa Nurul Hikmah; Chodidjah Chodidjah; Nur Anna Chalimah Sadyah (Litbang PWM Jawa Tengah, 2020)
This research aims to determine the effect of strenuous physical activity on the sum of leukocytes. The study used experimentally with the posttest only control group design approach. The study subjects of 10 male mice were randomly divided into two groups. The control group was not given heavy physical activity and the treatment group was given heavy physical activity. On the 27th day of blood retrieval for an examination of the sum of leukocytes in the Integrated Biomedical Laboratory, in July-August 2020. The mean on the sum of leukocytes increased in the treatment group compared to the control group. The Mann Whitney test showed that the sum of leukocytes in the control group was significantly different from the treatment group with a value of p = 0.009 (p <0.05). More research is needed on strenuous physical activity in IL-6 levels and calculates leukocytes as one of the study boosters. This research can be used as a reference in the control of the immune system of the body.